Nursing students' perception of spiritual and religious needs in hospitalized adult patients - Quispe Ramírez, Lisbeth Karolina; Nuela Masaquiza, Catalina Fernanda (Enfermería Cuidándote, 2025)
Introduction: Spirituality is a key component of well-being, recognized by the WHO as part of comprehensive health care. However, its approach in the hospital setting remains limited.Objective: To analyze the perception of nursing students about the spiritual and religious needs of adult patients hospitalized at the Technical University of Ambato. Specific: To evaluate the level of empathy of nursing students. To analyze how nursing students address spiritual and religious needs. To explore students' attitudes regarding the integration of spiritual and religious care.Methodology: Qualitative-quantitative study carried out with 64 seventh semester students. The Jefferson Empathy Scale was applied to measure the perception of spiritual care and a focus group to explore experiences and attitudes.Results: 48.4% of students had a medium level of empathy towards spiritual care, while 26.6% had low levels. Barriers such as lack of training, time and resources were identified. Most nurses believe that spiritual care strengthens the nurse-patient relationship, but they feel insecure about it due to the lack of practical training.Conclusion: Although students recognize the importance of spirituality in hospital care, their training in this area is insufficient. It is necessary to integrate practical content into the nursing curriculum to strengthen their ability to provide comprehensive and humanized care.
Keywords: Adults; Hospitalized Patients; Nursing; Patient-Centered Care; Religion; Spirituality